The Influence of Economic Development on the Wetland Conversion in Java-Bali - Wahyu Hidayati; Ihda Arifin Faiz (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2021)
While there have been evidences of successful economic development, certain Agriculture Industry show declining contributions to economy over recent years. There is a need for control of and policy on conversion of land status from agriculture to non-agriculture as a result of expanding economy. This research aims to analyse: (1) the impact of real GRDP, the number of households, the number of non-classified hotels and other types of accommodation businesses, and farmers’ terms of trade (FToT) on wetland conversion; (2) annual rate of wetland conversion; and (3) sustainability of food security after implementation of wetland conversion control. The data being analysed is pooled-data series 2014-2018 and cross sectional which is taken (provinces in Java-Bali). The result shows that the factors influencing wetland conversion negatively and significantly is real GRDP, the number of households and the number of non-classified hotels and other types of accommodation businesses are positively and significantly, whilst those affecting insignificantly is FToT. There is an upwards trend in wetland expansion, which indicates that agricultural land–instead of shrinking in area–is expanding at the rate of 40,574 hectares/year. It’s estimated that there will be 3,712,382 hectares of wetland by 2025. The tendency is followed by the growing number of rice surplus that reaches 909,922 tons/year. It’s projected that surplus in rice production by 2025 will be 17,404,632 tons. Consequently, management of renewable resources, prevention of wetland conversion, and prudent decision in rice import are as important as economic development. Keywords: wetland conversion, economic development, pooled-data